Epidemiology of injury and illness across all the competitive cycling disciplines: a systematic review and meta-analysis - Neil Heron; Debbie Palmer; Xavier Bigard; Thomas Fallon (BMJ Open Sport & Exercise Medicine, 2025)
Introduction The Union Cycliste Internationale, the world cycling governing body, has highlighted its mission to promote and support research in cycling epidemiology and medicine, especially for the benefit of lesser-known disciplines within its 2030 Agenda. This systematic review aimed to comprehensively analyse and synthesise the existing literature about cycling-related injuries and illnesses across all competitive disciplines.Design Systematic review and meta-analysis of epidemiological studies.Data sources PubMed (Medline), Embase and SPORTDiscus were searched in August 2024.Eligibility criteria All epidemiological studies including information on injuries and/or illness in competitive cycling from inception to August 2024.Results Forty-four studies were included across the competitive cycling disciplines of Mountain Bike (MTB), road, track, bicycle motocross (BMX) and para cycling. No studies were found for cyclocross, gravel, indoor, trials and esports cycling disciplines. BMX had the highest injury incidence overall, with 4.59 injuries per 365 days (95% CI 4.34 to 4.85), while para-cyclists had the highest illness prevalence at 3.89 illnesses per 365 days (95% CI 3.42 to 4.36). The most common injuries were upper limb injuries, particularly in BMX (65.21% (95% CI 54.50 to 74.65)), followed by road cycling (48.32% (95% CI 46.51 to 50.14)) and track cycling (44.18% (95% CI 43.28 to 45.09)). In road cycling, 14.36% (95% CI 13.12 to 15.69) of injuries were head, neck or face-related. Skin lacerations, abrasions and lesions were the most common injury types across disciplines, with bone fractures being the second most common. Despite a higher prevalence of head, neck and face injuries, road cycling had the lowest incidence of concussions (4.68% (95% CI 4.04 to 5.42)). Gastrointestinal illness had the highest prevalence overall in road cycling (17.90% (95% CI 14.4 to 22.0)), while respiratory illness was most prevalent in Track (31.82% (95% CI 22.29 to 42.61)) and MTB (31.82% (95% CI 22.29 to 42.61)).Conclusion This systematic review highlights the high prevalence of upper limb injuries across competitive cycling disciplines, particularly in BMX, road and track cycling. Skin lacerations, abrasions and bone fractures were the most common injury types. These findings help inform future injury and illness surveillance studies in cycling disciplines where high-quality epidemiological data are currently lacking and support the development of future injury and illness prevention strategies.PROSPERO registration number CRD42024502703.